A nickel-doped enhanced aluminum nitride ceramic and a preparation method thereof

By performing high-temperature demagnetization of nickel powder and using oxide sintering aids, combined with thermal isostatic pressure treatment, the ferromagnetic influence of nickel-doped aluminum nitride ceramic substrate and the problems of impurities during sintering are solved, and the ceramics are realized. High thermal conductivity and bending strength improvement.

CN116589293BInactive Publication Date: 2025-01-10GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202310578400.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is no relevant process information on nickel-doped aluminum nitride ceramic substrate in the prior art, which causes the ferromagneticity of nickel to affect the performance of ceramic substrates, and there are high temperature hazards and problems of impurity oxygen introduction during the sintering process.

Method used

By performing high-temperature demagnetization treatment on nickel powder, combined with oxide sintering aid and thermal isostatic treatment, nickel-doped enhanced aluminum nitride ceramics are prepared to avoid the ferromagnetic influence of nickel, reduce the sintering temperature and increase the ceramic Thermal conductivity and bending strength.

Benefits of technology

The aluminum nitride lattice is effectively purified, the thermal conductivity and bending strength are improved, the risk of sintering temperature is reduced, and the introduction of impurity oxygen is avoided, and nickel-doped reinforced aluminum nitride ceramics with excellent performance are prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004240847470000071
    Figure BDA0004240847470000071
Patent Text Reader

Abstract

The present invention discloses a nickel-doped enhanced aluminum nitride ceramic and a preparation method thereof, and relates to the technical field of ceramic additive manufacturing. In the preparation method of the nickel-doped enhanced aluminum nitride ceramic provided by the present invention, the nickel powder is first demagnetized at high temperature before nickel is added, thereby avoiding the influence of the ferromagnetism of nickel metal on the performance of the ceramic substrate; further introducing an oxide-type sintering aid can reduce the sintering temperature of the nickel-doped aluminum nitride, thereby avoiding the high temperature required during sintering causing certain hidden dangers to the equipment and workers, and helping to prepare aluminum nitride ceramics with high density, fine grains, and uniform microstructure; (3) In the preparation method of the present invention, by post-processing the sintered aluminum nitride ceramics with hot isostatic pressing, its bending strength can be further improved, thereby preparing the nickel-doped enhanced aluminum nitride ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic additive manufacturing, and in particular to a nickel-doped enhanced aluminum nitride ceramic and a preparation method thereof. Background Art

[0002] Aluminum nitride ceramics have excellent thermal conductivity (the theoretical value of thermal conductivity is about 320W·m -1 ·K -1 ), extremely high insulation (volume resistivity > 1012Ω·m), extremely low dielectric constant (about 8 at 1MHz) and dielectric loss, non-toxicity, and a thermal expansion coefficient that matches that of silicon (4.8×10 -6 K -1 ) and a series of excellent properties, and is considered to be an ideal heat dissipation and packaging material for the new generation of large-scale integrated circuits, semiconductor module circuits and high-power devices.

[0003] Metallic nickel is an iron-loving element, that is, it exists in the form of natural metal. At the same time, nickel has good wettability and corrosion resistance. The thermal conductivity of nickel is about 91W / (m·K). Because the aluminum nitride substrate needs to have good thermal conductivity and insulation, and nickel has extremely low resistivity and certain magnetism, it needs to be demagnetized to avoid affecting the performance of the ceramic substrate. The chemical wetting effect reaction of molten nickel is conducive to the removal of Al2O3 on the surface layer. Nickel doping can promote the formation of isolated second phases, thereby strengthening the grain boundaries of nickel-doped samples and improving their fracture toughness and bending strength.

[0004] However, there is no relevant process information on nickel-doped aluminum nitride ceramic substrates in the prior art. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a nickel-doped enhanced aluminum nitride ceramic and a preparation method thereof.

[0006] In order to solve the above problems, the present invention proposes the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a nickel-doped enhanced aluminum nitride ceramic, comprising the following steps:

[0008] S1, subjecting nickel powder to high temperature demagnetization treatment in a vacuum sintering furnace;

[0009] S2, taking 1-3 parts by mass of the nickel powder treated in step S1, 85-95 parts by mass of aluminum nitride powder, and 1-10 parts by mass of a sintering aid, and mixing them with a solvent and a dispersant to obtain a ceramic slurry;

[0010] S3, drying the ceramic slurry on a rotary evaporator to obtain a mixed powder, and sieving the mixed powder through a 50-120 mesh;

[0011] S4, subjecting the mixed powder to dry pressing and cold isostatic pressing to obtain an aluminum nitride ceramic green body;

[0012] S5, sintering the obtained ceramic green body in an atmosphere sintering furnace: first sintering at 500-800° C. for 1-2 hours, then heating to 1350-1500° C. for 1-5 hours;

[0013] S6. After sintering, hot isostatic pressing is performed to obtain nickel-doped enhanced aluminum nitride ceramics.

[0014] A further technical solution is that the specific operation of the hot isostatic pressing treatment is to perform the hot isostatic pressing treatment for 1 to 2 hours at a temperature 100 to 250° C. lower than the sintering temperature under N2 or Ar protective atmosphere.

[0015] A further technical solution is that the temperature of the hot isostatic pressing treatment is 1100-1300°C.

[0016] A further technical solution is that in step S1, the demagnetization temperature is 600-850° C. and the time is 0.5-1.5 hours.

[0017] It should be noted that in the present invention, the nickel powder needs to be demagnetized at high temperature in a vacuum environment in order to prevent the residual nickel powder from being magnetic due to the excess nickel and less oxygen during sintering, which is to be avoided for ceramic substrates.

[0018] A further technical solution is that the purity of the nickel powder is above 99.99%, and the particle size ranges from 0.5 to 3 μm.

[0019] A further technical solution is that the sintering aid is an oxide-type sintering aid.

[0020] A further technical solution is that the sintering aid is a rare earth oxide, such as Y2O3, La2O3, Ce2O3, and Dy2O3.

[0021] A further technical solution is that the mixing method in step S2 is one of magnetic stirring mixing, ultrasonic mixing, and ball milling mixing. Further explanation: since nickel powder itself has ferromagnetism, the present invention has demagnetized the nickel powder in step S1, so magnetic stirring can be used for mixing.

[0022] A further technical solution is that in step S4, the dry pressing process uses a pressure of 2-4 MPa, and positive and negative bidirectional pressing; the cold isostatic pressing pressure is 200 MPa, and the time is 300 seconds. Furthermore, the powder can be directly sieved into the dry pressing mold during sieving, and at the same time, the powder must be uniformly filled into the mold to reduce unexpected holes and cracks caused by uneven powder during dry pressing.

[0023] A further technical solution is that the solvent is one or more of anhydrous ethanol, isopropanol and n-butanol, and the dispersant is triethyl phosphate.

[0024] It should be noted that in step S3, in order to eliminate the solvent, a rotary evaporation method is used to dry the powder, the rotary evaporation temperature is 50-60°C, and the rotation speed is set at 20-50 rpm. This method can keep the slurry flowing and mixing, prevent sedimentation, and fully mix the nickel powder, sintering aid and aluminum nitride powder.

[0025] It should be noted that during sintering, the present invention is first sintered at 500-800°C for 1-2 hours under N2 or Ar protective atmosphere conditions to allow nickel to fully react with impurity oxygen and reduce the oxidation reaction of aluminum nitride, and then heated to 1350-1500°C for sintering for 1-5 hours; after sintering, the temperature is lowered to 1100-1300°C and hot isostatic pressing is performed for 1-2 hours; finally, the temperature is lowered to room temperature to obtain nickel-doped enhanced aluminum nitride ceramics. According to the prior art and literature records, by performing XRD phase analysis on the sample, it is predicted that there will be AlN, YAP, YAG, YAM and a small amount of NiO.

[0026] In a second aspect, the present invention provides a nickel-doped enhanced aluminum nitride ceramic, which is prepared by the preparation method described in the first aspect.

[0027] Compared with the prior art, the technical effects achieved by the present invention include:

[0028] The preparation method of the nickel-doped enhanced aluminum nitride ceramic provided by the present invention includes: (1) demagnetizing the nickel powder at high temperature to avoid the influence of the ferromagnetism of the nickel metal on the performance of the ceramic substrate; at the same time, the nickel is doped in the aluminum nitride to utilize the good wetting property of the nickel metal on the aluminum nitride, which can purify the lattice and thus improve the thermal conductivity of the aluminum nitride. Specifically, the addition of the Ni metal powder can promote the formation of the second phase (such as the YAM phase), because the second phase is small, uniform and isolated. The YAM phase formed at the grain boundary can remove the Al2O3 layer from the surface of the AlN grain and combine more oxygen at the grain boundary, thereby reducing the content of impurity oxygen in the AlN lattice, purifying the AlN lattice and improving the thermal conductivity; (2) The introduction of the oxide-type sintering aid in the present invention can, on the one hand, reduce the sintering temperature of nickel-doped aluminum nitride, thereby avoiding the high temperature required during sintering, which poses certain hidden dangers to equipment and workers; on the other hand, compared with the fluoride-type sintering aid, the oxygen contained in the oxide-type sintering aid will not produce additional impurities to the sintered body to affect the performance, which is helpful for preparing aluminum nitride ceramics with high density, fine grains and uniform microstructure; (3) In the preparation method of the present invention, by post-treating the sintered aluminum nitride ceramics by hot isostatic pressing, its bending strength can be further improved, thereby preparing nickel-doped enhanced aluminum nitride ceramics.

[0029] The preparation provided by the invention has low cost, good product performance, improved production efficiency of enterprises, and has certain practical commercial value and realistic significance. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments are described clearly and completely below. Obviously, the embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0032] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.

[0033] Example 1

[0034] This embodiment provides nickel-doped enhanced aluminum nitride ceramics and a preparation method thereof. The composition of the ceramic powder is as follows: 93 parts by mass of aluminum nitride powder, 3 parts by mass of nickel powder, and 4 parts by mass of sintering aid. The slurry solvent is anhydrous ethanol, accounting for 60% of the total weight of the main phase material and the sintering aid, and the dispersant is triethyl phosphate, accounting for 2% of the total weight of the main phase material and the sintering aid. Among them, the purity of the nickel powder is above 99.99%, and the particle size range is 0.5 to 3μm. The sintering aid is Y2O3 with a purity of more than 99.99%.

[0035] The specific preparation process is as follows:

[0036] S1, subjecting the nickel powder to a high temperature demagnetization treatment at 770°C in a vacuum sintering furnace for 1 hour;

[0037] S2, mixing aluminum nitride powder, nickel powder, sintering aid, solvent and dispersant, and mixing by magnetic stirring to prepare ceramic slurry;

[0038] S3, drying the ceramic slurry on a rotary evaporator at a temperature of 60°C and a rotation speed of 40 rpm, sieving the dried powder through a 100-mesh sieve and directly sieving it into a dry pressing mold;

[0039] S4, the sieved powder is loaded into a mold, and first subjected to positive and negative bidirectional pressure pressing at a pressure of 3 MPa; then subjected to cold isostatic pressing at a pressure of 200 MPa for 300 seconds to obtain an aluminum nitride ceramic green body;

[0040] S5, sintering the obtained ceramic green body in an atmosphere sintering furnace under a N2 / Ar gas atmosphere, first sintering at 700°C for 1.5 hours, and then continuing to heat up to 1350°C for 5 hours;

[0041] S6. After sintering, hot isostatic pressing post-treatment is performed: in N2 or Ar protective atmosphere, hot isostatic pressing is performed at a temperature of 1150°C for 1.5 hours to obtain nickel-doped enhanced aluminum nitride ceramics, which are sample 1 and sample 2. The size of sample 1 is 4.0 mm × 3.0 mm × 36 mm, and the size of sample 2 is 10 mm × 10 mm × 2.0 mm.

[0042] Example 2

[0043] The present embodiment provides nickel-doped enhanced aluminum nitride ceramics and a preparation method thereof. The composition of the ceramic powder is as follows: 93 parts by mass of aluminum nitride powder, 1 part by mass of nickel powder, and 6 parts by mass of sintering aid. The solvent for slurrying is anhydrous ethanol and isopropanol, and the volume ratio of anhydrous ethanol: isopropanol is 1:1, accounting for 60% of the total weight of the main phase material and the sintering aid. The dispersant is triethyl phosphate, accounting for 2% of the total weight of the main phase material and the sintering aid. The purity of the nickel powder is above 99.99%, and the particle size range is 0.5 to 3 μm. The sintering aid is Y2O3 with a purity of more than 99.99%.

[0044] The specific preparation process is as follows:

[0045] S1, subjecting the nickel powder to a high temperature demagnetization treatment at 770°C in a vacuum sintering furnace for 1 hour;

[0046] S2. Aluminum nitride powder, nickel powder, sintering aid, solvent and dispersant are mixed and mixed by ball milling to prepare ceramic slurry; specifically, the ceramic slurry is obtained by ball milling at a speed of 300 rpm for 10 hours on a planetary ball mill. Zirconia balls are used as ball milling balls, and the ball-to-material ratio is 2:1.

[0047] S3, drying the ceramic slurry on a rotary evaporator at a temperature of 50°C and a rotation speed of 50 rpm, and sieving the dried powder through a 100-mesh sieve;

[0048] S4, the sieved powder is loaded into a mold, and first subjected to positive and negative bidirectional pressure pressing at a pressure of 4 MPa; then subjected to cold isostatic pressing at a pressure of 200 MPa for 300 s to obtain an aluminum nitride ceramic green body;

[0049] S5, sintering the obtained ceramic green body in an atmosphere sintering furnace under a N2 / Ar gas atmosphere, first sintering at 800°C for 1 hour, and then continuing to raise the temperature to 1500°C and sintering for 3.5 hours;

[0050] S6. After sintering, hot isostatic pressing post-treatment is performed: in N2 or Ar protective atmosphere, hot isostatic pressing is performed at a temperature of 1300°C for 2 hours to obtain nickel-doped enhanced aluminum nitride ceramics, which are sample 1 and sample 2. The size of sample 1 is 4.0mm×3.0mm×36mm, and the size of sample 2 is 10mm×10mm×2.0mm.

[0051] Comparative Example 1

[0052] The difference from Example 1 is that the preparation process of Comparative Example 1 lacks step S1, that is, Comparative Example 1 does not perform high-temperature demagnetization treatment on the nickel powder. The remaining material proportions and preparation process are the same as those of Example 1.

[0053] Comparative Example 2

[0054] The difference from Example 1 is that the sintering aid of Comparative Example 2 is a fluoride type sintering aid, specifically YF3. The rest of the material ratios and preparation process are the same as those of Example 1.

[0055] Comparative Example 3

[0056] The difference from Example 1 is that the average particle size of the nickel powder in Comparative Example 3 is in the range of 5 to 10 μm. The rest of the material ratios and preparation process are the same as those in Example 1.

[0057] Comparative Example 4

[0058] Different from Example 1, in step S5 of Comparative Example 4, the sintering process is specifically to heat the obtained ceramic green body to 1350° C. and sinter for 5 hours in an atmosphere sintering furnace under N2 / Ar gas atmosphere. The rest of the material ratios and preparation process are the same as those in Example 1.

[0059] Comparative Example 5

[0060] Different from Example 1, in step S5 of Comparative Example 5, the sintering process is specifically as follows: the obtained ceramic green body is sintered in an atmosphere sintering furnace under a N2 / Ar gas atmosphere, first sintered at 700°C for 1.5 hours, and then continued to heat up to 1800°C and sintered for 5 hours. The rest of the material proportions and preparation process are the same as those in Example 1.

[0061] Comparative Example 6

[0062] The difference from Example 1 is that the hot isostatic pressing treatment in step S6 is missing in Comparative Example 6. That is, after the sintering in step S5 is completed, the nickel-doped enhanced aluminum nitride ceramic is obtained in Comparative Example 6, and the rest of the material ratios and preparation process are the same as those in Example 1.

[0063] Comparative Example 7

[0064] Different from Example 1, the composition of the ceramic powder of Comparative Example 7 is as follows: 95 parts by mass of aluminum nitride powder, 0.5 parts by mass of nickel powder, and 4.5 parts by mass of sintering aid. The rest of the material ratios and preparation process are the same as those of Example 1.

[0065] Comparative Example 8

[0066] Different from Example 1, the composition of the ceramic powder of Comparative Example 8 is as follows: 88 parts by mass of aluminum nitride powder, 6 parts by mass of nickel powder, and 6 parts by mass of sintering aid. The rest of the material ratios and preparation process are the same as those of Example 1.

[0067] The nickel-doped enhanced aluminum nitride ceramic samples prepared in the above examples and comparative examples were subjected to performance tests, wherein sample 1 was used to test bending strength, fracture toughness and density, and sample 2 was used to test thermal conductivity and dielectric loss properties. The results are shown in Table 1.

[0068] Table 1 Performance test results of aluminum nitride ceramic substrate

[0069]

[0070]

[0071] It can be seen from the results in Table 1 that the nickel-doped enhanced aluminum nitride ceramics and preparation methods thereof provided in Examples 1 and 2 avoid the influence of the ferromagnetism of nickel metal on the performance of the ceramic substrate by demagnetizing the nickel powder at high temperature. Compared with the performance of Comparative Example 1, the ferromagnetism of the nickel powder will reduce the thermal conductivity, bending strength, fracture toughness and dielectric properties of the ceramic substrate. Therefore, for nickel-doped aluminum nitride ceramics, it is necessary to demagnetize the nickel metal.

[0072] Comparative Example 2 uses a fluoride-type sintering aid, but the thermal conductivity, bending strength, and fracture toughness of the nickel-doped aluminum nitride ceramic obtained are significantly lower than those of Example 1 and Example 2, indicating that the fluoride-type sintering aid will introduce additional fluorine, and the fluorine may remain in the aluminum nitride in the form of other impurities during the sintering process, thereby reducing the thermal conductivity, bending strength, and fracture toughness; while the present invention specifically uses an oxide-type sintering aid, and the fate of the oxygen introduced into the sintering aid can refer to the impurity oxygen introduced during sintering, and no additional impurities will be generated to affect the performance.

[0073] The nickel powder added in Comparative Example 3 has a larger particle size and a smaller specific surface area. The obtained nickel-doped aluminum nitride ceramics are not as good as those in Examples 1 and 2 in terms of density, thermal conductivity, bending strength, fracture toughness, etc., indicating that the particle size of the added nickel powder should be as small as possible and should not be too large.

[0074] In step S5 of comparative example 4, the process of sintering at a low temperature is lacking, so that nickel and impure oxygen cannot fully react, resulting in more oxidation reactions of aluminum nitride, and the overall performance of the obtained nickel-doped aluminum nitride ceramics is poor.

[0075] In step S5 of comparative example 5, due to the excessively high sintering temperature and the excessively long sintering time, the grains grow abnormally, thereby reducing the thermal conductivity and bending strength of the material.

[0076] After the sintering in step S5 is completed, the comparative example 6 obtains the nickel-doped enhanced aluminum nitride ceramic, which lacks the hot isostatic pressing treatment. According to the data of Examples 1 and 2, it can be seen that the post-hot isostatic pressing treatment can further eliminate the pores and improve the density and strength. Therefore, the bending strength of the comparative example 6 is lower than that of other schemes.

[0077] The amount of nickel powder added in Comparative Example 7 is relatively low, and the enhancement effect of nickel on the thermal conductivity, bending strength, etc. of aluminum nitride ceramics is not obvious.

[0078] The proportion of nickel powder added in Comparative Example 8 is relatively high. For aluminum nitride substrates, adding a certain amount of nickel powder (1 to 3 parts by mass) can help improve the thermal conductivity and flexural strength of the aluminum nitride substrate. However, when the proportion of nickel powder is too high, it will reduce the thermal conductivity and flexural strength of the aluminum nitride substrate. Therefore, the amount of nickel powder added should not be too high.

[0079] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0080] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing nickel-doped enhanced aluminum nitride ceramics, characterized in that: The following steps are involved: S1, subjecting the nickel powder to a high-temperature demagnetization treatment in a vacuum sintering furnace, the demagnetization temperature being 600-850° C. for 0.5-1.5 hours; S2, taking 1-3 parts by mass of the nickel powder treated in step S1, 85-95 parts by mass of aluminum nitride powder, and 1-10 parts by mass of a sintering aid, and mixing them with a solvent and a dispersant to obtain a ceramic slurry; the sintering aid is an oxide-type sintering aid; S3, drying the ceramic slurry on a rotary evaporator to obtain a mixed powder, and sieving the mixed powder through a 50-120 mesh; S4, subjecting the mixed powder to dry pressing and cold isostatic pressing to obtain an aluminum nitride ceramic green body; S5, sintering the obtained ceramic green body in an atmosphere sintering furnace: first sintering at 500-800°C for 1-2 hours, then heating to 1350-1500°C for 1-5 hours; S6. After sintering is completed, hot isostatic pressing is performed to obtain nickel-doped enhanced aluminum nitride ceramics; the specific operation of the hot isostatic pressing is to perform hot isostatic pressing for 1 to 2 hours at a temperature 100 to 250° C. lower than the sintering temperature under N2 or Ar protective atmosphere.

2. The method for preparing the nickel-doped enhanced aluminum nitride ceramic according to claim 1, characterized in that: The temperature of the hot isostatic pressing treatment is 1100-1300°C.

3. The method for preparing the nickel-doped enhanced aluminum nitride ceramic according to claim 1, characterized in that: The purity of the nickel powder is above 99.99%, and the particle size ranges from 0.5 to 3 μm.

4. The method for preparing the nickel-doped enhanced aluminum nitride ceramic according to claim 1, characterized in that: The sintering aid is a rare earth oxide.

5. The method for preparing the nickel-doped enhanced aluminum nitride ceramic according to claim 1, characterized in that: In step S4, the pressure of the dry pressing process is 2-4 MPa, and the pressing is performed in both positive and negative directions; the pressure of the cold isostatic pressing is 200 MPa, and the time is 300 s.

6. The method for preparing the nickel-doped enhanced aluminum nitride ceramic according to claim 1, characterized in that: The solvent is one or more of anhydrous ethanol, isopropanol and n-butanol, and the dispersant is triethyl phosphate.

7. A nickel-doped enhanced aluminum nitride ceramic, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Particle dispersion toughening aluminum nitride ceramic substrate and preparation method thereof

    CN103553691A

  • Preparation method of aluminum nitride / diamond polycrystalline material

    CN112047740A

Cited By

  • High-toughness high-thermal-conductivity aluminum nitride ceramic and production process thereof

    CN120590171A

  • High-toughness high-thermal-conductivity aluminum nitride ceramic and production process

    CN120590171B